DECISION SUPPORT SYSTEM WITH MABAC METHOD TO DETERMINE THE BEST STUDENTS - Rima Tamara Aldisa; Ahmad Rifqi (Adisam Publisher, 2024)
This research aims to apply the Multi Attributive Border Approximation Area Comparison (MABAC) method in the process of selecting the best students in the educational environment. MABAC, as a multi-criteria decision making method, provides a systematic and objective approach to evaluating and comparing various attributes possessed by students. In this study, the criteria considered include academic, extracurricular, personality and social skills aspects. Data was collected from academic records, teacher assessments, and observations of student involvement in school activities. The MABAC method is used to calculate the relative weight of each criterion and determine a comprehensive score for each student. The research results show that the MABAC method is effective in providing a holistic and multifaceted assessment of student performance. In addition, this method also helps in identifying strengths and areas of development for each student, thereby providing valuable insight for teachers and educators in the coaching process. This research concludes that the application of MABAC can be a useful tool in the educational evaluation process, especially in determining the best students with a more objective and structured approach.